2007
DOI: 10.1002/bjs.5881
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition after oesophageal cancer surgery in Sweden

Abstract: Malnutrition is a considerable problem after oesophagectomy, and is linked to appetite loss, eating difficulties and odynophagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 18 publications
1
89
0
Order By: Relevance
“…Further details of the studies are given in Table 1. In general, all studies were considered deficient in one or more aspects of their study design/ reporting, which increased the likelihood of bias. In terms of selection, no eligibility criteria were reported in two studies [17,26], one prospective study used consecutive patients attending outpatient clinics [18] and all others used convenient samples from defined time periods [19][20][21][22][23][24][25][27][28][29][30][31][32][33]. Participation rate was reported in 16 of the 18 studies, and ranged between 66 and 100%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further details of the studies are given in Table 1. In general, all studies were considered deficient in one or more aspects of their study design/ reporting, which increased the likelihood of bias. In terms of selection, no eligibility criteria were reported in two studies [17,26], one prospective study used consecutive patients attending outpatient clinics [18] and all others used convenient samples from defined time periods [19][20][21][22][23][24][25][27][28][29][30][31][32][33]. Participation rate was reported in 16 of the 18 studies, and ranged between 66 and 100%.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies considered the frequency of malnutrition, defined by a greater than 10% or 15% loss of baseline weight [21,28,29,32] These found that at six and 12 months after surgery, more than half of the patients had lost more than 10% of their initial weight.…”
Section: Changes In Nutritional Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 7 summarizes the studies reporting on the most common patient symptoms after surgery. 4,11,42,[44][45][46][47][48][49][50][51][52][53] These indicate a high prevalence of gastrointestinal symptoms. In studies reporting at 12 months or more, symptoms were seen with the following frequency: dumping syndrome 15%-75% (median 46%), dysphagia 11%-38% (median 27%), early satiety 40%-90% (median 65%) and reflux symptoms 19%-61% (median 29%).…”
Section: Later Challenges Nutrition and Weightmentioning
confidence: 99%
“…Occurrence of these symptoms can contribute to weight loss and are detrimental to the overall nutritional status of patients [2][3][4][5]. Furthermore, use of adjunctive chemo-and radio-therapy either before or after surgery may further exacerbate these symptoms.…”
Section: Introductionmentioning
confidence: 99%